Brigittenau by the Prater in Vienna - Unknown:::Creator::::::::::::; Meyer, Joseph, 1796-1856 (author):::Contributor:::::::::::: (Hildburghausen; Kunstanst d. Bibliographisches Institut; Germany)
Engraving with a view of the Brigittenau near the Prater in Vienna